Fructan synthesis, accumulation and polymer traits. II. Fructan pools in populations of perennial ryegrass (Lolium perenne L.) with variation for water-soluble carbohydrate and candidate genes were not correlated with biosynthetic activity and demonstrated constraints to polymer chain extension - Gallagher, Joe A.; Cairns, Andrew J.; Thomas, David; Timms-Taravella, Emma; Skøt, Kirsten; Charlton, Adam; Williams, Peter; Turner, Lesley B. (Frontiers in Plant Science, 2015)
Differences have been shown between ryegrass and fescue within the Festulolium subline introgression family for fructan synthesis, metabolism and polymer-size traits. It is well-established that there is considerable variation for water-soluble carbohydrate and fructan content within perennial ryegrass. However there is much still to be discovered about the fructan polymer pool in this species, especially in regard to its composition and regulation. It is postulated that similar considerable variation for polymer traits may exist, providing useful polymers for biorefining applications. Seasonal effects on fructan content together with fructan synthesis and polymer-size traits have been examined in diverse perennial ryegrass material comprising contrasting plants from a perennial ryegrass F2 mapping family and from populations produced by three rounds of phenotypic selection. Relationships with copy number variation in candidate genes have been investigated. There was little evidence of any variation in fructan metabolism across this diverse germplasm under these conditions that resulted in substantial differences in the complement of fructan polymers present in leaf tissue at high water-soluble carbohydrate concentrations. The importance of fructan synthesis during fructan accumulation was unclear as fructan content and polymer characteristics in intact plants during the growing season did not reflect the capacity for de novo synthesis. However, the retention of fructan in environmental conditions favouring high sink / low source demand may be an important component of the high sugar trait and the roles of breakdown and turnover are discussed.